Facades modules for eco-efficient refurbishment of buildings : an overview - Sacht, Helenice Maria (2010)
The search for new technologies for energy efficiency in buildings is urgent once conventional technologies currently used in the refurbishment of buildings, in the most cases are not efficient. The work presents the initial studies about a new facade system: "Facade Modules for Eco-Efficient Refurbishment of Buildings". It is expected to be a new technology among the new and growing set of products that will solve the need for functional and aesthetic demands. These new elements should result in a modular system, capable of being used combined or separately with simple, flexible and versatile application procedures. Initial studies and simulations in Design Builder software were done having as object a cell (25 m²) with different arrangement of facade modules with passive and current solutions to Guimarães city. Preliminary results show a decrease of energy consumption in the analyzed cases, representing an advantage from passive solar systems and the reduction of energy consumption.